2006
DOI: 10.1111/j.1479-6988.2006.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of oral health recommendations into two residential aged care facilities in a regional Australian city

Abstract: Background Residents of aged care facilities usually have a large number of oral health problems. Residents who suffer from dementia are at particular risk. A systematic review of the best available evidence with regard to maintaining the oral health of older people with dementia in residential aged care facilities provided a number of recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 30 publications
0
48
0
1
Order By: Relevance
“…However, studies on the effectiveness of such strategies are limited [43]. Professional factors and individual characteristics identified in our scoping review including lack of dementia-specific knowledge, resistance to change, held attitudes, staff engagement and competence also appear to play a role in the implementation of dementia care practices [32, 4448]. This indicates that future implementation efforts would benefit from a preparation stage to identify potential barriers and facilitators, and subsequently plan for multifaceted strategies that address the different levels informed by the needs and desires of relevant stakeholders in a constantly changing environment of care provision.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the effectiveness of such strategies are limited [43]. Professional factors and individual characteristics identified in our scoping review including lack of dementia-specific knowledge, resistance to change, held attitudes, staff engagement and competence also appear to play a role in the implementation of dementia care practices [32, 4448]. This indicates that future implementation efforts would benefit from a preparation stage to identify potential barriers and facilitators, and subsequently plan for multifaceted strategies that address the different levels informed by the needs and desires of relevant stakeholders in a constantly changing environment of care provision.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, studies have also reported no improvements (Reed et al, 2006), especially long term. Interestingly, Fallon et al (2006) found the implementation of various teaching formats with a strong emphasis on practical skills was more effective in improving oral health knowledge absorption. However, these findings raise intriguing questions regarding a lack of historical requests for oral health education by the participants, given their apparent self-reporting of a deficit in knowledge and skills.…”
Section: Discussionmentioning
confidence: 99%
“…Although the National Oral Health Plan 2004-2013 (National Advisory Committee on Oral Health 2004) and subsequent educational strategies (Fallon et al 2006;Chalmers et al 2009) recognised the critical roles that could be played by HCPs in providing oral health care in RACFs, our review indicated a series of policy/protocol, educational, attitudinal, geographic/ environmental, health, access/equity, research and resource barriers that limit effective communication and collaboration between HCPs (Table 1).…”
Section: Oral Care Provision Barriersmentioning
confidence: 96%